2022
DOI: 10.1101/2022.05.16.22275074
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Jinhua Qinggan Granules for Nonhospitalized COVID-19 Patients: a Double-Blind, Placebo-Controlled, Randomized Controlled Trial

Abstract: BackgroundKey findings from the World Health Organization Expert Meeting on Evaluation of Traditional Chinese Medicine in treating COVID-19 reported that TCMs are beneficial, particularly for mild-to-moderate cases. The efficacy of Jinhua Qinggan Granules (JHQG) in COVID-19 patients with mild symptoms has yet to be clearly defined.MethodsWe conducted a phase 2/3, double-blind, randomized, placebo-controlled trial to evaluate the efficacy and safety of treatment with JHQG in mild, nonhospitalized, laboratory-co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Secondly, the SARS-CoV-2 strain of the patients included in this study is partially different from the currently prevalent SARS-CoV-2 Omicron variant in clinical features (such as infectivity and immune escape) [31]. However, considering the wide applicability of TCM and the exact curative effect on various variant strains, the results of this study can still provide evidence to support the current treatment of COVID-19 and new respiratory infectious diseases in the future [32].…”
Section: Discussionmentioning
confidence: 84%
“…Secondly, the SARS-CoV-2 strain of the patients included in this study is partially different from the currently prevalent SARS-CoV-2 Omicron variant in clinical features (such as infectivity and immune escape) [31]. However, considering the wide applicability of TCM and the exact curative effect on various variant strains, the results of this study can still provide evidence to support the current treatment of COVID-19 and new respiratory infectious diseases in the future [32].…”
Section: Discussionmentioning
confidence: 84%
“…We recently completed a double-blind, placebo-controlled, randomized controlled trial conducted in non-hospitalized Pakistani patients with mild COVID-19 infection ( 12 ). The findings, under review, demonstrated that early administration of JHQG led to effective relief of viral infection symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, JHQG has been utilized in the treatment of the H1N1 influenza, and has been shown to effectively alleviate symptoms and promote recovery among influenza patients ( 10 , 11 ). Our group was involved in a recent study that demonstrated that JHQG was effective in promoting recovery from COVID-19 related symptoms and suppressing acute phase reactants in a group of Pakistani patients with mild COVID-19 infections ( 12 ). Nonetheless, there is currently no evidence in the literature to evaluate the efficacy of JHQG in the reduction of hospitalization and mortality of COVID-19 patients who are at high risk of progression.…”
Section: Introductionmentioning
confidence: 99%